Bunaken (Bisnis Unggulan Nugget Kenjeran) as diversification of preparation of a shell to improve state community revenue - Dina Nafa Hanifah; Fitri Ratna Juwita; Afida Kholifatunnisa (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2019)
The country of Indonesia is a maritime country with a vast ocean greater than the land area. It is from this Indonesian sea that there are various types of marine catches that can be used as a source of income by communities around the coast. Ordinary coastal communities work as fishermen or sellers of marine catches. However, until now the utilization of the catch is still not optimal. This is indicated by the low level of coastal economy. The community of Kedung Cowek, Kenjeran has prospective potential to produce processed seafood products. Shellfish are abundant marine products in the area. But the use of shellfish by local people is still not optimal. Usually the catch of shellfish is sold to collectors. Sea products in the form of shellfish in the Kedung Cowek area have the potential to be processed into high-quality and nutritious preparations. The aim of this program is to increase public knowledge about varied and high-selling shellfish processing with sustainable training, to improve public understanding of good and profitable marketing management and to create diversified shellfish processing to increase the income of the Kedung Cowek community. The method is carried out by conducting training on shellfish processing, seaweed, attractive packaging, and marketing. Periodic assistance is carried out to carry out ongoing coaching. Thus, it is expected that the community in the Kedung Cowek area will be able to make nutritious and high-selling shellfish preparations and can increase income.